2000
DOI: 10.1021/om0006211
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Tris- and Cyclic Silylhydroxylamines from Trimeric and Tetrameric Lithium N,N-Bis(silyl)hydroxylamides

Abstract: The fluorosilylhydroxylamine tBuSiF(Me)−ONH2 (2) is obtained in the reaction of tBuSiF(Me)−NHtBu (1) and HONH2·HCl. The reaction of tBuSiMe2−ONH2 with butyllithium leads to the formation of the bis(silyl)hydroxylamine tBuSiMe2−NH−O−SiF(Me)tBu (3). Depending on the bulkiness of the substituents and the solvent, lithium salts of N,O-bis(silyl)hydroxylamines crystallize as dimeric, trimeric, or tetrameric O-lithium-N,N-bis(silyl)hydroxylamides, e.g., [(tBuSiMe2)2N−OLi·THF]2, [(tBuSiMe2)2N−OLi]3 (4), and [tBuSiMe2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…(5) The lithium salt of N,O-bis(tert-butyldimethylsilyl)hydroxylamine crystallises from THF as dimeric N,N-bis(tertbutyldimethylsilyl)hydroxylamide [7] and reacts with trifluoro-(phenyl)silane at 0°C with formation of N,N-bis(tert-butyldimethylsilyl)-O-[difluoro(phenyl)silyl]hydroxylamine (2). (6) Product 2 could be isolated following the removal of LiF in a centrifuge by virtue of the low reaction temperature and the bulky SiMe 2 CMe 3 groups.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…(5) The lithium salt of N,O-bis(tert-butyldimethylsilyl)hydroxylamine crystallises from THF as dimeric N,N-bis(tertbutyldimethylsilyl)hydroxylamide [7] and reacts with trifluoro-(phenyl)silane at 0°C with formation of N,N-bis(tert-butyldimethylsilyl)-O-[difluoro(phenyl)silyl]hydroxylamine (2). (6) Product 2 could be isolated following the removal of LiF in a centrifuge by virtue of the low reaction temperature and the bulky SiMe 2 CMe 3 groups.…”
Section: Resultsmentioning
confidence: 99%
“…The softer Lewis acid F 2 SiPh migrates to the softer Lewis base nitrogen, while the harder Lewis acid SiMe 2 CMe 3 migrates to the harder Lewis base oxygen. (7) When heated under reflux for 3 d, 1 and 3 undergo a thermal rearrangement to form the silylaminodisiloxanes 4 and 5, respectively. The conversion of 1 to 4 was monitored by 1 H NMR spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lithiation of Bu t SiMe 2 ONHSiMe 2 Bu t in the presence of tmen results in cleavage of the N-O bond and formation of (Bu t SiMe 2 OLi) 6 . 81 An Xray diffraction study revealed a rare example of an (LiO) 4 ladder in the structure of {[PhC(O)N(Me)Al(Me)(Bu t )OMe]Li[PhC(O)N(Me)Al(Me)(OBu t )OMe]Li} 2 . 82 Reaction of a-cyanophosphonates (RO) 2 P(O)CH 2 CN (R = Et or Pr i ) with LiNPr i 2 in thf has yielded the Wittig-type reagents [N•CCH(RO) 2 P(O)Li(thf)] H the structures of which are based on Li 2 O 2 rings which link up through inter-dimer association via the nitrile group to form cross-linked polymeric networks.…”
Section: Oxygen-and Sulfur-donor Ligandsmentioning
confidence: 99%